Being an Educator and Game Developer: The Role of Pedagogical Content Knowledge in Non-Commercial Serious Games Production. (December 2019) - Linderoth, Jonas; Sjöblom, Björn
Background and aim . Previous literature has discussed tensions between the field ofgame design and the field ofeducation . It has been emphasized that it is important to address this tension when developinggame based learning (GBL) . In order to find potential ways of approaching this problem, we investigate the development ofGBL when performed by those who have both pedagogical content knowledge (PCK) and experience in game development. Method . Twocase studies about serious games production were conducted, a game section at a national defense college and a university course in educational game design. The cases, as well as individual development projects within the settings, were analyzed with a focus on the role of PCK during serious games development. Results . While the developers and instructors at the defence college, who designed games for their in-house needs, had both PCK and knowledge about game development, these competencies varied a lot among the participants at the university course. The results show that educational goals added complexity to the design process. By comparison, some studied game projects at the university course avoided this complexity. These projects legitimized their games as educational by suggesting unproven far transfer. In other cases, where the developers did have PCK, the instructional goals where taken as a starting point that guided the whole development process. This lead to games that were designed to match highly specific educational contexts. The developers, instructors and teachers in both of the settings who used their PCK tended to break a number of established game design heuristics that would have been counter productive in relation to the learning objectives of the games. Conclusions . The paper suggests that there is a need for people withpedagogical content knowledge AND knowledge aboutgame development. Enhancing these dual competencies in game workers could forward the field of GBL.